2019
DOI: 10.1002/iub.2013
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxycamptothecin Prevents Fibrotic Pathways in Fibroblasts In Vitro

Abstract: Peritendinous fibrosis, which leads to impaired tendon function, is a clinical problem worldwide, and it is urgent to explore potential ways to reduce the formation of peritendinous adhesion. Several studies have demonstrated the biological roles of hydroxycamptothecin (HCPT) in inhibiting fibrosis in different tissues. In this study, we investigated whether HCPT could inhibit tendon fibrosis in vitro. Our results revealed that HCPT inhibited transforming growth factor (TGF)‐β1‐induced cell viability of human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…These data indicates that the ATF-6 partial pathway is activated and involved in the inhibition of fibrosis by HCPT. Based on our previous research (Yao et al, 2019) and the above findings, the potential pathway by which HCPT inhibits tendon fibrosis is presented in Figure 7 .…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations
“…These data indicates that the ATF-6 partial pathway is activated and involved in the inhibition of fibrosis by HCPT. Based on our previous research (Yao et al, 2019) and the above findings, the potential pathway by which HCPT inhibits tendon fibrosis is presented in Figure 7 .…”
Section: Resultsmentioning
confidence: 88%
“…Our previous studies demonstrated that HCPT regulates proliferation and apoptosis in fibroblast and thus has the potential to prevent tendon adhesion (Yao et al, 2019). In this study, using a rat tendon injury model, we observed that 0.1 mg/ml HCPT significantly inhibited peritendinous adhesion 3 weeks after injury.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This phenomenon is a normal part of the wound healing process after tissue injury or surgical repair (Chen et al., 2019; Hsu et al., 2018). Although adhesion is an essential step during surgical wound healing, excessive progression can cause severe postoperative adhesion at the operated site, which is accompanied by several complications such as a limited range of motion, pain, loss of function, and the need for additional surgery (e.g., tenolysis and scar release) (Chou et al., 2017; Yao, Zheng, Zhang, et al., 2019). Particularly, postoperative peritendinous adhesion (PPA) is often caused by physical trauma involving the flexor digitorum profundus or flexor digitorum superficialis tendons (Chen et al., 2014; MengQing et al., 2020).…”
Section: Introductionmentioning
confidence: 99%